Indonesian Rheumatology Association (IRA) Recommendations for Diagnosis and Management of Osteoarthritis (Knee, Hand, Hip) - Rakhma Yanti Helmi; Najirman; Ida Ayu Ratih Wulansari Manuaba; Andri Reza Rahmadi; Pande Ketut Kurniari; Malikul Chair; Ika Vemilia Warlisti; Eka Kurniawan; Harry Isbagio; Handono Kalim; Rudy Hidayat; Laniyati Hamijoyo; Cesarius Singgih Wahono; Sumariyono (Indonesian Journal of Rheumatology, 2023)
Background: Osteoarthritis (OA) is the most common form arthritis in the world, and its prevalence is predicted to rise higher in the future due to increasing life expectancy and growing number of elderly population. With the emergence of new treatment options in the last several years, a better understanding of OA diagnosis and management is required by every physician in Indonesia. Methods: A panel of eight selected rheumatologists from the Indonesian Rheumatologist Association (IRA) developed recommendations based on key questions formulated by a steering committee from IRA. These recommendation materials were taken from several online databases such as PubMed, Science Direct, and Google Scholar. Level of evidence and grades of recommendation were then assigned, and each member of the panelist team will assign a score to express their level of agreement. Results: A total of 25 recommendations discussing the diagnosis, pharmacological and non-pharmacological therapies, as well as monitoring for OA were formulated. Conclusion: These recommendations can be used to help clinicians in accurately diagnosing OA and choosing the most suitable therapy for their patients. All recommendation statements were tailored to the clinical setting, facility, and drug availability in Indonesia.